Dual targeting of the cancer antioxidant network with 1, 4-naphthoquinone fused Gold(i) N-heterocyclic carbene complexes. Issue 9 (28th July 2017) - McCall, R.; Miles, M.; Lascuna, P.; Burney, B.; Patel, Z.; Sidoran, K. J.; Sittaramane, V.; Kocerha, J.; Grossie, D. A.; Sessler, J. L.; Arumugam, K.; Arambula, J. F.
Abstract : Herein, we report a simple and rational approach to the design of a targeted therapy ( i.e., complex1 ) whose mechanism of action involves targeting a single cancer relevant pathway via two independent mechanisms. Abstract : To achieve a systems-based approach to targeting the antioxidant pathway, 1, 4-naphthoquinone annulated N-heterocyclic carbene (NHC) [bis(1, 3-dimesityl-4, 5-naphthoquino-imidazol-2-ylidene)-gold(i )] [silver(i ) dichloride] (1 ), [bis(1, 3-dimesityl-4, 5-naphthoquino-imidazol-2-ylidene)-gold(i )] chloride (2 ), and 1, 3-dimesityl-4, 5-naphthoquino-imidazol-2-ylidene)-gold(i ) chloride (3 )) were designed, synthesized, and tested for biological activity in a series of human cancer cell lines. The solution phase of complexes1–3 were assigned using several spectroscopy techniques, including NMR spectroscopic analysis. Complexes1 and3 were further characterized by single crystal X-ray diffraction analysis. Electrochemical and spectroelectrochemical studies revealed that quinone reductions are reversible and that the electrochemically generated semiquinone and quinone dianions are stable under these conditions. Complex1, containing two NHC-quinone moieties (to accentuate exogenous ROS via redox cycling) centered around a Au(i ) center (to inactivate thioredoxin reductase (TrxR) irreversibly), was found to inhibit cancer cell proliferation to a much greater extent than the individual components ( i.e., Au(i )–NHC alone or naphthoquinone alone). Treatment of A549 lung cancer cells with1 produced a 27-fold increase in exogenous reactive oxygen species (ROS) which was found to localize to the mitochondria. The inhibition of TrxR, an essential mediator of ROS homeostasis, was achieved in the same cell line at low administrated concentrations of1 . TrxR inhibition by1 was similar to that of auranofin, a gold(i ) containing complex known to inhibit TrxR irreversibly. Complex1 was found to induce cell death via an apoptotic mechanism as confirmed by annexin-V staining. Complex1 was demonstrated to be efficacious in zebrafish bearing A549 xenografts. These results provide support for the suggestion that a dual targeting approach that involves reducing ROS tolerance while concurrently increasing ROS production can perturb antioxidant homeostasis, enhance cancer cell death in vitro, and reduce tumor burden in vivo, as inferred from preliminary zebra fish model studies.